Short Communication Proximate Composition of Head of Wild and Farmed Catla catla - Nadeem, Amana; Liaqat, Farhana; Hussain, Bilal; CEPS, K. Iqbal (Biological Sciences - PJSIR, 2008)
. In the study for finding out the proximate composition of head of wild and farmed Catla catla, the moisture contents were recorded as 63.06 ± 0.46% and 54.91 ± 0.53%, protein contents as 14.77 ± 0.37% and 19.92 ± 0.44%, lipids contents as 7.56 ± 0.46% and 11.90 ± 0.25%, ash contents as 12.26 ± 0.52% and 12.40 ± 0.31% and total nitrogen free extract as 2.31 ± 0.05% and 0.74 ± 0.03%, respectively. Thus farmed fish contained more lipid and protein contents as compared to that of wild fish.